Temporal and morphologic characteristics of pinopod expression across the secretory phase of the endometrial cycle in normally cycling women with proven fertility - Usadi, Rebecca S.; Murray, Michael J.; Bagnell, Robert C.; Fritz, Marc A.; Kowalik, Ania I.; Meyer, William R.; Lessey, Bruce A. (Fertility and sterility, 2003)
To assess the temporal and morphologic characteristics of pinopod expression on the surface of endometrium across the secretory phase, in LH-timed endometrial samples in normal, healthy women. Prospective, randomized study. Academic teaching hospital. Sixty-eight healthy volunteers with proven fertility. Urinary LH-timed endometrial and blood sampling was performed on each subject on a randomly selected day of the secretory phase. Histologic dating, assessment of pinopods using scanning electron microscopy, and comparison with serum P levels. Eighty-six endometrial tissue samples obtained from 68 subjects were evaluated under scanning electron microscopy. Pinopods were first observed on luteal day 5, corresponding with the onset of the midluteal phase increase in serum P levels. Pinopods persisted for the entire duration of the secretory phase, but their morphology changed as the cycle advanced. The present findings demonstrate that pinopods are a characteristic feature of the mid to late secretory phase endometrial epithelium, exhibit cycle-dependent changes in morphology, and are most prominent during the putative implantation interval.